FACTORS OF ELECTRONIC MONEY USE IN CROWDED BUYING AND SELLING TRANSACTIONS AT THE TAKJIL RAMADHAN MARKET IN KUTIM DISTRICT USING GROUNDED THEORY - Adi Setiawan; Panka Gumilang; Rudi Setiari; Jerry Heikal (Jurnal Media Akademik (JMA), 2024)
Technological developments have affected the social behaviour of society, the existence of technological advances is marked by the emergence of revolutions 1.0 to 4.0 which is one of the factors that greatly affects the pattern of life. Revolution 4.0 produces an assumption that the industrial revolution is not only disrupting the technological field, but has penetrated the social, economic and legal fields, and to deal with disruption due to the industrial revolution, it is necessary to have a humanities study that will monitor technological progress in order to remain in the prevailing humanitarian norms (Mumtaha & Khoiri, 2019).. The industry is constantly changing and developing rapidly. Technology and Information is the most important point in today's industrial world. Companies are required to move quickly and provide innovations to adjust to this. one of the industries that is developing in accordance with technology is digital wallet (e-wallet). With technology is a digital wallet (e-wallet). The emergence of digital wallets as a means of payment online transactions that are easy and practical have made many Indonesians start switching to using the application. The application has increased the number of users every year The rapid growth with various advantages provided makes it easy to transact without using physical money and provides a sense of security in the transaction process. The value of digital payment transactions also grows from year to year, considering the growth of new MSMEs and the development of technology and social media makes the need for transactions. This research uses qualitative techniques with a grounded theory approach. The author conducted direct interviews with several business people and buyers in the food and beverage sector in the month of Ramadan to find out the effect of electronic money in increasing transactions. Based on the results of the study, it was found that the coding scheme consisted of 8 codes that formed 4 categories and gave rise to 3 themes with a total frequency of 8. The highest frequency in coding was 5 on the theme of socialisation constraints and 2 on the theme of network constraints, the last was 1 on the theme of complicated transactions so that the factors that cause the non-use of digital wallets in buying and selling transactions in business actors in the MSME sector in East Kalimantan, especially East Kutai district, are socialisation constraints in increasing transaction volumes in a number of MSMEs that continue to grow.